Effects of Optimizing the Scan-Path on Scanning Keyboards with QWERTY-Layout for English Text - Sandnes, Frode Eika; Medola, Fausto Orsi [UNESP] (IOS Press, 2017)
Scanning keyboards can be essential tools for individuals with reduced motor function. However, most research addresses layout optimization. Learning new layouts is time-consuming. This study explores the familiar QWERTY layout with alternative scanning paths intended for English text. The results show that carefully designed scan-paths can help QWERTY nearly match optimized layouts in performance.
Keywords: assistive technologies; reduced motor function; Scanning keyboard; text entry